2010
DOI: 10.1016/j.chembiol.2010.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Siderophores from Neighboring Organisms Promote the Growth of Uncultured Bacteria

Abstract: Summary The majority of bacterial species do not grow on synthetic media. Many non-growers require growth factors from other bacteria, but the nature of these compounds is largely unknown. We show here that previously uncultured isolates from marine sediment biofilm grow on a Petri dish in the presence of cultured organisms from the same environment. The growth factors produced by one cultured helper strain were identified as new acyl-desferrioxamine siderophores. A panel of previously uncultured isolates exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
332
1
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 399 publications
(352 citation statements)
references
References 62 publications
15
332
1
4
Order By: Relevance
“…The role played by siderophores in nature is believed to be so fundamental that the inability of microorganisms to produce such compounds may be a major cause of microbial uncultivability. 2 This suggests that the survival of a large percentage of microorganisms on Earth may depend on neighbouring siderophore-producing species. 2 Iron plays essential roles in house-keeping functions such as DNA replication, protein synthesis and respiration, and siderophore-mediated iron uptake is specifically associated with many other biological processes such as fungal sexual development 3 and germination, 4 plant growth promotion, 5 pilus formation, 6 and pathogen virulence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role played by siderophores in nature is believed to be so fundamental that the inability of microorganisms to produce such compounds may be a major cause of microbial uncultivability. 2 This suggests that the survival of a large percentage of microorganisms on Earth may depend on neighbouring siderophore-producing species. 2 Iron plays essential roles in house-keeping functions such as DNA replication, protein synthesis and respiration, and siderophore-mediated iron uptake is specifically associated with many other biological processes such as fungal sexual development 3 and germination, 4 plant growth promotion, 5 pilus formation, 6 and pathogen virulence.…”
Section: Introductionmentioning
confidence: 99%
“…2 This suggests that the survival of a large percentage of microorganisms on Earth may depend on neighbouring siderophore-producing species. 2 Iron plays essential roles in house-keeping functions such as DNA replication, protein synthesis and respiration, and siderophore-mediated iron uptake is specifically associated with many other biological processes such as fungal sexual development 3 and germination, 4 plant growth promotion, 5 pilus formation, 6 and pathogen virulence. 7,8 In a study by Ueda and colleagues on terrestrial antibiotic-producing streptomycetes, it was reported that morphological development (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…To assess the commonality of the growth dependence of uncultured organisms on neighboring species and pick good models for study, we chose an environment where bacteria live in a tightly packed community. 45 This is a biofilm that envelopes sand particles of a tidal ocean beach (Figures 7a and b). After disrupting the biofilm, cells were Microorganisms as a source of secondary metabolites K Lewis et al plated on nutrient medium containing sterile seawater (R2Asea).…”
Section: Growth Factorsmentioning
confidence: 99%
“…Through these and similar studies we have come to recognize specific mechanisms of interaction, which can occur in the marine environment, such as facilitation of iron uptake (Amin et al, 2009;D'Onofrio et al, 2010), transfer of essential vitamins (Croft et al, 2005), inter-and intra-specific communication (Bassler and Losick, 2006;Vardi et al, 2006) and allelopathy (Mayali et al, 2008;Hibbing et al, 2009). Hypothesizing that bacterium-bacterium antagonistic interactions shape microbial community structure at the microscale, Long and Azam (2001) analyzed interactions among 86 pairs of co-isolated marine bacteria on solid media, revealing the widespread distribution of the potential for growth inhibition among these bacterial strains (Long and Azam, 2001;Grossart et al, 2004;Rypien et al, 2009).…”
Section: Introductionmentioning
confidence: 99%